Program Trauma Healing bagi Anak Korban Kekerasan Seksual di DP3APM Kota Pekanbaru Tahun 2023 - Ricno Harlius; Fakhri Usmita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Trauma healing programs for child victims of violence are crucial because they can help them recover physically, emotionally, and psychologically. Children who experience sexual violence are at risk of experiencing long-term trauma that impacts their mental and social development. This study aims to determine the implementation of the Trauma Healing Program for child victims of sexual violence, which was implemented by the Pekanbaru City Department of Women's Empowerment, Child Protection, and Community Empowerment (DP3APM) in 2023. This study used a qualitative approach with in-depth interviews. Seven informants participated in this study: the Head of DP3APM, the Head of the UPT PPA, community members, and a psychiatrist. This study found that the trauma healing program encompasses three main stages. First, the security and stabilization stage (establishing safety), carried out by providing compassionate therapy and support to the victim's parents. Second, the remembering and grieving stage (remembering and grieving), carried out by gathering information from the victim and providing healing therapy to restore their mental state. Third, the connecting and integrating stage (reconnection), which helps victims accept their condition and return to normal life. For victims whose condition remains unstable, the healing program will continue. The main obstacle to implementing this program is budget constraints, particularly for logistical needs such as accommodation, food, and transportation. Despite this, the trauma healing program conducted by the Pekanbaru DP3APM has been well-implemented and has provided victims with a gradual and structured response and recovery effort. The main obstacle to implementing this program is budget constraints, particularly in providing facilities such as housing, daily meals, and transportation.